DISTRIBUSI EBONI ( Diospyros spp. ) DI KAWASAN PUSAT PEYELAMATAN SATWA TASIKOKI - Andikha P. Lamada; Johny S. Tasirin; Marthen T. Lasut (COCOS, 2016)
ABSTRACTThe purpose of this research was to determine the number and species distributionof ebony (Diospyros spp.) at the Animals Rescue Center of Tasikoki. This study wasconducted in North Minahasa Regency, District of Kauditan, Village of Watudambo whichconducted for 6 months, from March to September 2015. Data collcetion was conductedby using the census method, all types of vegetation that resembles the species of ebony(Diospyros spp.) which are located in the area of Animals Rescue Center of Tasikoki wereobserved, which starting from a predetermined point until the entire region was observed.The results of data collection in the field, have been found two species of ebony (Diospyrosspp.), namely Diospyros maritima and Diospyros ebenum with the total of 1864 rods forDiospyros maritima and 63 rods for Diospyros ebenum. To Diospyros maritima wasdivided into four phases of growth, i.e. 1499 at the seedling stage, 249 at stake phase, 98in pole phase, and 18 in tree phase. Most of that four phase of growth, was found in dryand non-flouded areas which adjacent to the coastline in the region. Diospyros ebenum wasdivided into three phases of growth, namely 4 in the seedling phase, 54 in sapling phase,and 5 in poles phase. Most of that three phase of growth also found in dry and non-floadedareas which adjacent to the coastline in the region of Animals Rescue Center of Tasikoki.Keywords: Diospyros spp., species distribution, phase of growth, Animals RescueCenter of Tasisoki.